Effect of amino-defective-MOF materials on the selective hydrodeoxygenation of fatty acid over Pt-based catalysts - Phan, Dieu Phuong; Le, Van Nhieu; Nguyen, Thuy Ha; Kim, Han Bom; Park, Eun Duck; Kim, Jinsoo; Lee, Eun Yeol (Journal of Catalysis, 2021)
With the aim of developing more efficient catalysts based on MOF materials for biomass upgrading through the hydrodeoxygenation, a novel Pt/UiO-66-based catalyst was first designed by introducing amino groups, together with creating mixing-linker defect using 5-amino-isophthalic acid as a mixed linker, were successfully synthesized with a microwave-solvothermal method. XPS and CO-chemisorption measurements revealed that the presence of amino groups significantly enhance the reducibility of the PtCl62- and PtCl42- phases to the Pt0 phase. As a result, the catalytic performance of these catalysts in the HDO of oleic acid was enhanced, as demonstrated by the 1.8–3.2-fold higher turnover frequency compared to the original Pt/UiO-66 catalyst. Interestingly, the presence of amino-defective linker facilitated the transition from decarbonylation to the hydrodeoxygenation reaction, as confirmed by the significant increase in C18/C17 ratio. Importantly, the modified catalysts were shown to possess a good catalytic stability, thus preventing coke deposition on the UiO-66 structure.
Keywords: Catalytic performance; Catalytic stability; Efficient catalysts; Hydrodeoxygenation; Modified catalysts; Pt-based catalyst; Solvothermal method; Turnover frequency; Hydrodeoxygenation; Microwave-assisted solvothermal method; Oleic acid; Pt-based catalysts; UiO-66 material